Application of two-sample Mendelian randomization method to assess the causal relationship between rheumatoid arthritis and osteoporotic fracture - Zhenyu, Cai; Le, Chang; Shiyong, Zeng; Jinding, Lin; Mingzhong, Liu; Haifeng, Tang; Rongdong, Zeng (Frontiers in Medicine, 2024)
Background The association between rheumatoid arthritis (RA) and osteoporotic fracture has garnered considerable attention; however, the causal relationships between diseases remain uncertain. Therefore, this study employed Mendelian randomization (MR) analysis to investigate the causal effects of RA on osteoporotic fracture. Methods The summary data for RA and osteoporotic fracture were extracted from the genome-wide association studies (GWAS) catalog and the Finn Biobank database. The database provides information about diseased and health control subjects. We searched the database for the following conditions: RA, osteoporosis (OP), and osteoporotic fractures. Entries were published by investigating centers, which had established definitions and diagnostic criteria. We downloaded and processed the data to obtain the single-nucleotide polymorphisms (SNPs) strongly associated with RA, OP, and osteoporotic fracture. RA genetic associations were obtained from the GWAS catalog, including 1961 cases and 454,387 controls. The osteoporosis of the GWAS catalog involved 991 cases and 455,357 controls, and the data of the Finn Biobank involved 8,017 cases and 391,037 controls. Genetic associations for osteoporotic fracture were taken from the Finn Biobank of 1822 cases and 311,210 controls. Independent SNPs that are significantly associated with meeting the criteria of p < 5 × 10–8, r2 < 0.001, and kb = 10,000 were selected for MR analysis. The inverse variance-weighted (IVW) method along with other MR methods was employed for analysis, while sensitivity analyses were conducted to assess reliability and stability. Results The results provided strong evidence that RA was causally and positively associated with osteoporosis from the GWAS catalog (OR = 1.16590; 95% CI: 1.04067–1.30619; p = 0.00811) and the Finn Biobank database (OR = 1.07314; 95% CI: 1.03455–1.11317; p = 0.00016). Moreover, a positive causal relationship was detected between RA and osteoporotic fracture (OR = 1.10132; 95% CI: 1.00506–1.20680; p = 0.03863). The results were robust according to sensitivity tests. Conclusion This study showed positive causal relationships between RA and osteoporotic fracture. These results should be considered in further studies and public health measures on osteoporosis prevention strategies.